Loss of interaction between plectin and type XVII collagen results in epidermolysis bullosa simplex. Issue 12 (6th October 2017) - Natsuga, Ken; Nishie, Wataru; Nishimura, Machiko; Shinkuma, Satoru; Watanabe, Mika; Izumi, Kentaro; Nakamura, Hideki; Hirako, Yoshiaki; Shimizu, Hiroshi
Abstract: Plectin is a linker protein that interacts with intermediate filaments and β4 integrin in hemidesmosomes of the epidermal basement membrane zone (BMZ). Type XVII collagen (COL17) has been suggested as another candidate plectin binding partner in hemidesmosomes. Here, we demonstrate that plectin–COL17 binding helps to maintain epidermal BMZ organization. We identified an epidermolysis bullosa (EB) simplex patient as having markedly diminished expression of plectin and COL17 in skin. The patient is compound heterozygous for sequence variants in the plectin gene ( PLEC ); one is a truncation and the other is a small in‐frame deletion sequence variant. The in‐frame deletion is located in the putative COL17‐binding domain of plectin and abolishes the plectin–COL17 interaction in vitro. These results imply that disrupted interaction between plectin and COL17 is involved in the development of EB. Our study suggests that protein–protein binding defects may underlie EB in patients with unidentified disease‐causing sequence variants. Abstract : Plectin is a linker protein that interacts with intermediate filaments and β4 integrin in hemidesmosomes of the epidermal basement membrane zone (BMZ). Type XVII collagen (COL17) has been suggested as another candidate plectin binding partner in hemidesmosomes. Here, we demonstrate that plectin‐COL17 binding helps to maintain epidermal BMZ organization and that disrupted interaction between plectin and COL17 is involved in the development of epidermolysis bullosa.